Implementasi Profil Pelajar Pancasila Beriman Bertakwa Kepada Tuhan Dan Berakhlak Mulia Pada Kesantunan Barbahasa - Cicik paramida Paramida; Muhammad Abduh (Elementary Teacher Education Program, Majalengka University, 2023)
Language has a very important function to learn, with the language it can communicate with others, therefore in communicating it is necessary to use polite language. Nowadays children speak using impolite language and speak rudely, thus this study aims to implement the profile of pancasila students who believe in fearing God Almighty and have noble morals. Research conducted with qualitative research with a case study approach. Data collection techniques are interviews, observation and documentation. The classes taken were class IV, V, VI and each class was taken by 5 children randomly. The data analysis techniques used in this study are data collection, data reduction, data presentation, and conclusions. The results of the research are the implementation of the profile of pancasila students, who believe in God Almighty and have noble morals can provide teaching